Quality Characteristics of Some Algerian Olive Oils with Antioxidant Activity - Boudjema, S; LACHRAF, A; Fella, L; TOUARFIA, M; HABERRA, S (My University)
Herein, the physicochemical properties of ten samples of olive oil from various Algerian regions (the acidity, peroxide, and saponi¦cation index, the speci¦c extinction coe¨cient (K232, K270), the content of chlorophyll, carotenoids, and total polyphenols), in addition to their antioxidant activity were investigated and were compared with three other control samples. The physicochemical characteristics of the tested olive oils proved oil quality varying from virgin to extra virgin olive oil of excellent nutritious and healthy quality for the consumer according to the commercial standards recommended by the International Olive Council (IOC). Moreover, the olive oil collected samples showed that the antioxidant activity of oil samples from south Algeria (Sahara) is higher than that of Northern Algeria, and the oils of Chemlal variety exhibited higher antioxidant activity than that of Segoise variety.